The Influence of Gibberellic Acid (GA3) Application and Partial Coating on Pre and Postharvest Performance of Grapefruit - Nisar, Sara; Samad, Nadia; Mukhtar, Sidra; Qazi, Imran; Ali, Qazi Shoaib; Zahir, Ayesha; Zeb, Nagina; Shah, Hajra; Khattak, Muhammad Sohaib; Khan, Shehla Gul (Indus Journal of Bioscience Research, 2025)
Gibberellic acid (GA3) a widely used plant growth regulator is involved in regulating the processes of growth and development such as, vegetative growth, bud dormancy, fruit set, increasing yield, fruit quality, fruit ripening and optimization of fruit storage. This study was conducted at Horticulture Research Farm, and Postharvest Laboratory, The University of Agriculture Peshawar, during winter (2018-19). Pre-harvest research trial was planned as Randomized Complete Block Design (RCBD) having one factor. GA3 foliar spray of different concentrations, i.e 0, 15, 30 and 45 ppm were applied on grapefruits. Two factorial experiment by using Completely Randomized Design (CRD) was carried out in laboratory. Grapefruits were partially coated with coconut oil and stored for 60 days. Data was taken at 20 days interval. Results showed that GA3 concentrations significantly influenced all the quality attributes. Fruits treated with 45 ppm GA3 showed maximum days to maturity, number of fruits tree-1, yield tree-1 (kg), with less total soluble solids (oBrix), maximum ascorbic acid (mg.100g-1), less reducing sugars (%), maximum non-reducing sugars (%) and least weight loss (%). All the quality attributes were significantly influenced by various intervals of storage, which showed maximum total soluble solids (oBrix), with less ascorbic acid (mg.100g-1), maximum reducing-sugars (%), less non-reducing-sugars (%) and maximum weight loss (%) were recorded in fruits stored for 60 days. The interactive effect of storage duration and GA3 concentrations exhibited non-significant effect on all attributes except weight loss and ascorbic acid. It is inferred that grapefruits can be sprayed with 45 ppm GA3 at physiological maturity stage and coated with coconut oil to better retain the quality attributes and increase the storability of fruits.